Impact of Mobile and Online Banking on the Access of Crypto Currency on Tertiary Level Students (Journal of Green Business School, 2025)
This study explores the impact of online banking in the access of crypto currency among the tertiary level of students in the context of Bangladesh. Though Bangladesh Bank doesn’t allow holding and trading any kind of virtual currency like Bitcoin, Ethereum, Ripple, and Litecoin, moreover it is illegal in Bangladesh. Many people in our country, especially students from the tertiary level trade in cryptocurrency. Most of them use mobile transactions and online banking like Bkash, Rocket, Nagad, etc. to make the transaction on Cryptocurrency though the total numbers of users are unidentified. This study aims to find out the impact of mobile and online banking on the accessibility to cryptocurrency. Mixed method research has been conducted for exploring the impact of mobile and online banking on access to cryptocurrency through various online platforms of students from the tertiary level, age group ranging from 18-30 years. This study shows that despite the ethical issues, the youth of Bangladesh are investing their own country's assets in cryptocurrency. Also, there is a bit of confusion about the exact amount of assets that have been or are being invested in this cryptocurrency. This study has some limitations the cryptocurrency is still treated as a new type of trade in Bangladesh. Yet it shows the access and interest of tertiary-level students in crypto platforms. As this virtual currency is the world’s future, we Bangladeshis have to cope with this virtual currency by solving this issue.J. of Green Business. Sch. Vol 6(1), Jan-Dec, 2023; pp 116-128